Performance evaluation of J2EE & .NET web services interacting with a .NET client - Nakka, Raja Sanjeev Kumar (Kansas State University, 2007)
The objective of this project is to build an e-commerce website using ASP.NET as well as J2EE technologies. Visual Studio 2005 provides a great IDE to build seamless front end layer for the websites with minimum effort. Hence, it is used to build the presentation layer. The business logic layer is developed in ASP.NET 2.0 and J2EE, exposing the functions as web services. Two similar clients have been developed in ASP.NET. These two clients invoke the .NET and J2EE web services. The two similar websites are subjected to testing for correctness and performance. Stress and load testing is performed thoroughly on the website. A detailed analysis of the results is done using the response times and throughputs from various tests. This report proves that we can build a website using a presentation tier developed in ASP.NET consuming any of the two technologies’ (ASP.NET & J2EE) web services. This proves to be very useful in scenarios where we need the best overall user experience regardless of the technology, to replace or extend an existing business tier by using a different technology.
Keywords: .NET; web services; Computer Science (0984)